Insights into the Beginnings and Glory of Romanian Gerontology - Baran, Dana (DELTOS, 2024)
Romanian medicine has made significant early contributions to modern gerontology and geriatrics. Understanding, integrating and combating old age was in keeping not only with ancient mythology and old Romanian fairy-tales, but also with the scientific approaches to the art of prolonging life, or macrobiotics, which emerged in the 19th century. In the 20th century, several Romanian doctors focused on gerontology and geriatrics, a research area directly related with the progress of neurology, endocrinology and physiology. Professors Gheorghe Marinescu, Constantin I. Parhon and Ana Aslan, along with Grigore Benetato, all members of the Romanian Academy, as well as Dr. Dimu Kotsovsky were among these scientists interested in age study and management. Institutes, publications and medico-social establishments were designed for this purpose. Today, Romania is striving to revitalise its rich tradition of gerontology and geriatrics in alignment with current international standards.